2017
DOI: 10.1016/j.ijggc.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Cost and performance of some carbon capture technology options for producing different quality CO 2 product streams

Abstract: A techno-economic assessment of power plants with CO2 capture technologies with a focus on process scenarios that deliver different grades of CO2 product purity is presented.The three leading CO2 capture technologies are considered, namely; oxyfuel combustion, pre-combustion and post-combustion capture. The study uses a combination of process simulation of flue gas cleaning processes, modelling with a power plant cost and performance calculator and literature values of key performance criteria in order to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 26 publications
(26 reference statements)
0
31
0
1
Order By: Relevance
“…According to this study, the assumptions which were used for plant performance and costs were showed similarity. However, it is noted that fuel prices and price trends were very different between the US and Europe [45] [47]. The quality of the coal used directly affects the performance and cost of the power plant.…”
Section: Operating and Maintenance Labormentioning
confidence: 99%
“…According to this study, the assumptions which were used for plant performance and costs were showed similarity. However, it is noted that fuel prices and price trends were very different between the US and Europe [45] [47]. The quality of the coal used directly affects the performance and cost of the power plant.…”
Section: Operating and Maintenance Labormentioning
confidence: 99%
“…The model comprises five sub-models: a supercritical coal-fired power plant model, a CaL system model, a secondary steam cycle model, an ASU model and a CPU model. The main model follows the work of Hanak et al [26] , but has the additional features that the previously used by other authors [30] with positive results.…”
Section: The New System Conceptmentioning
confidence: 99%
“…The CO 2 capture technology has been widely used for gas purification in the chemical and oil refining industries over several decades [1][2][3][4][5][6]. To mitigate CO 2 emissions from point sources, post-combustion CO 2 capture (PCC) using amines has been recognized as a promising technology because the process can remove the massive CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several technologies were developed to remove these products, using ultraviolet light, ozone, and water-wash methods [14][15][16]. However, technologies for NH 3 removal have not been studied, although the product causes serious problems to humans such as an increase in anaerobic glycolysis, blood sugar, and blood lactic acidosis by inhibiting the citric acid cycle. In addition, NH 3 can react with sulfur oxides and nitrogen oxides in the atmosphere to generate ultrafine particles such as ammonium sulfate and ammonium nitrate.…”
Section: Introductionmentioning
confidence: 99%